2010
DOI: 10.1152/ajpheart.00365.2009
|View full text |Cite
|
Sign up to set email alerts
|

VEGF and soluble VEGF receptor-1 (sFlt-1) distributions in peripheral arterial disease: an in silico model

Abstract: Vascular endothelial growth factor (VEGF) is a key regulator of angiogenesis, the growth of new capillaries from existing microvasculature. In peripheral arterial disease (PAD), lower extremity muscle ischemia develops downstream of atherosclerotic obstruction. A working hypothesis proposed that the maladaptive overexpression of soluble VEGF receptor 1 (sVEGFR1) in ischemic muscle tissues, and its subsequent antagonism of VEGF bioactivity, may contribute to the deficient angiogenic response in PAD, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 86 publications
3
48
0
Order By: Relevance
“…18 VEGF 165 and VEGF 121 interactions with their receptors (VEGFR 1 and VEGFR 2 ) and nonsignaling neuropilin-1 coreceptor have been extensively studied using validated computational models in the context of angiogenesis, 17,[19][20][21][22] including models relevant to PAD. 19,22,23 These models have demonstrated that in the absence of neuropilin-1, VEGF 165 and VEGF 121 behave similarly. When present, however, neuropilin-1 enhances the binding of VEGF 165 to VEGFR 2 , which is a major mediator of the angiogenic effects of VEGF-A.…”
Section: Laboratory Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…18 VEGF 165 and VEGF 121 interactions with their receptors (VEGFR 1 and VEGFR 2 ) and nonsignaling neuropilin-1 coreceptor have been extensively studied using validated computational models in the context of angiogenesis, 17,[19][20][21][22] including models relevant to PAD. 19,22,23 These models have demonstrated that in the absence of neuropilin-1, VEGF 165 and VEGF 121 behave similarly. When present, however, neuropilin-1 enhances the binding of VEGF 165 to VEGFR 2 , which is a major mediator of the angiogenic effects of VEGF-A.…”
Section: Laboratory Analysismentioning
confidence: 97%
“…17 Such models have also demonstrated that VEGF concentration in blood, but not in tissue, is dependent on the vascular permeability of healthy tissue. 17,23,83 The net arteriogenic/angiogenic effects of measured VEGF isoforms (165 and 121) would also be influenced by other VEGF isoforms and receptors not assessed in this study. These include the VEGF xxx b isoforms, generated through alternative splicing, which are generally antiangiogenic.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the predictive power of these models has previously been limited by insufficient knowledge of cell surface receptor levels. Therefore, the data that we report here provide critical parameters needed to advance systems biology models of ischemic disease (7,27,49,58,75).…”
Section: Cd31mentioning
confidence: 99%
“…Computational models, based on mass-action kinetics of the VEGF-VEGFR signaling axis, have predicted the distribution of soluble VEGFR1 in peripheral vascular disease (75) and the distribution of VEGF within diseased tissue, healthy tissue, and blood (67), and a recent computational model has included in vitro-and ex vivo-derived VEGFR surface levels on the endothelium (23). This experimentally associated model provided insights into the pharmacokinetics of an anti-VEGF agent in the treatment of metastatic breast cancer and suggested novel neoadjuvant treatment approaches (23,36,37).…”
mentioning
confidence: 99%